T243. MENTAL HEALTH SERVICE UTILIZATION IN YOUNG ADULTS REPORTING PSYCHOSIS-LIKE EXPERIENCES. (18th May 2020) - Bridgwater, Miranda; Rouhakhtar, Pamela Rakhshan; Klaunig, Mallory; Petti, Emily; Roemer, Caroline; Andorko, Nicole; DeLuca, Joseph; Pitts, Steven; Mittal, Vijay; Vargas, Teresa; Schiffman, Jason
Abstract: Background: Psychosis-like experiences (PEs) may reflect elevated risk for the onset of serious mental illness, such as a psychotic disorder, as well as negatively impact functioning. Few studies have examined the relation between PEs and mental health service utilization or intent to seek treatment. Characterizing psychosis risk and service utilization among individuals in the peak developmental period for psychotic disorders ( ages 18–25) may help the field improve psychosis screening tools and reduce the duration of untreated illness. Methods: Participants (N = 439) were individuals between the ages of 18 and 25 years old (M = 20.24) who completed an online survey regarding their mental health experiences. They completed the PRIME Screen with distress and self-reported mental health service utilization throughout their lifetime and for the past two months. Participants were asked how strongly they were considering seeking mental health treatment (Likert-type scale, response options ranging from 1 ["Not at all"] to 5 ["Very much"]). The PRIME Screen symptom total score, total distress score, and specific item responses were used in bivariate correlations and a multiple linear regression model. Results: Approximately a third of the participants (34%) screened positively on the PRIME, mean total score of 16.67 (SD = 14.53). Sixteen percent of participants reported seeking mental health treatment in the past two months, and 38% reported they were currently considering seeking treatment. There were no significant correlations between mental health service utilization in the past two months and PRIME symptom total score (p = .31), or distress total score (p = .32). PRIME total scores and PRIME distress total scores were also not significantly associated with lifetime utilization of mental health services (p = .22 and p =.45, respectively). There were significant relations between how strongly participants were considering seeking mental health treatment and both PRIME symptom total (r = 0.20, p < .01, N = 413) and distress total scores (r = 0.20, p < .01, N = 359). A multiple linear regression model indicated certain PRIME items contributed significantly to this relation (PRIME items 1[odd/unusual experiences], 3[thought control], 6[mind reading], and 12[concerns with "going crazy"]; all ps < .05). Follow-up analyses showed that distress associated with PRIME items 1, 3 and 12 was significantly higher (all ps < .01) than the mean PRIME distress item score. Discussion: Results suggest that while a third of a college sample of young adults scored positively on the PRIME screen, PEs and related distress were not significantly related to lifetime or current mental health service utilization. Among those not already seeking services, however, both PEs symptom and distress were significantly associated with participants' intent to utilize mental health treatment. Thus, individuals may experience distressing PE symptoms, but many do not receive mental health services. Higher endorsement of and distress with experiences relating to: odd/unusual experiences, thought control, mind reading, and concern with "going crazy" were more closely associated with intent to seek treatment, suggesting that specific PEs may increase individuals' desire to address these concerns via mental health services. Findings highlight the need to identify and engage individuals not yet in treatment who have frequent/high level, distressing, and specific PEs.